Educational level and risk profile of cardiac patients in the EUROASPIRE II substudy. Issue 1 (18th December 2003) - Mayer, O; Šimon, J; Heidrich, J; Cokkinos, D V; De Bacquer, D
Abstract : Study objective: To ascertain, whether, conventional risk factors and readiness of coronary patients to modify their behaviour and to comply with recommended medication were associated with education in patients with established coronary heart disease. Design and methods: EUROASPIRE II was a cross sectional survey undertaken in 1999–2000 in 15 European countries to ascertain how effectively recommendations on coronary preventions are being followed in clinical practice. Consecutive patients, men and women ⩽71 years who had been hospitalised for acute coronary syndrome or revascularisation procedures, were identified retrospectively. Data were collected through a review of medical records, interview, and examination at least six months after hospitalisation. The education reached was ascertained at the interview. Main results: A total of 5556 patients (1319 women) were evaluated. Significantly more patients with ischaemia had only primary education, in contrast with the remaining diagnostic groups. Body mass index and glucose were negatively associated with educational level, while HDL-cholesterol was positively associated. Men with highest education had significantly lower systolic blood pressure and total cholesterol. The prevalence of current smoking decreased significantly from primary to secondary and high education only in men. Both men and women with primary educational level were more often treated with antidiabetics, and antihypertensives, but less often with lipid lowering drugs. The effectiveness of treatment was virtually the same in all education groups. Conclusions: Patients with higher education had lower global coronary risk, than those with lower education. This should be considered in clinical practice. Particular strategies for risk communication and counselling are needed for those with lower education status.